Life Trajectory of the University of Baguio Teaching Employees: Pre-retirees Anxieties and Preparation and Retirees’ Life Conditions and Satisfaction - Julius A. Simon (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research study explored the life trajectory of teaching employees at the University of Baguio, focusing on pre-retiree anxieties and preparations and retirees' life conditions and satisfaction. A quantitative survey questionnaire gathered data from pre-retiring employees aged 50–59 and retired employees. Findings indicated slight anxieties and satisfaction with preparations among pre-retirees. Retired employees faced challenges in living conditions, particularly regarding financial security, health status, and social status, but expressed high satisfaction. The study underscored the importance of institutional programs to address retirement factors, enhance preparations, and improve overall living conditions and satisfaction. Valuable insights were provided for administrators, human resource managers, and policymakers to develop effective strategies and programs. Further research is recommended to explore additional factors impacting post-retirement well-being.